Green Supply Chain Management: The Key to Sustainable Competitive Advantage - Fadel Hilmi; Erfan Arif, M. (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to investigate the implementation of Green Supply Chain Management (GSCM) and its effect on the competitive advantage of PT Gudang Baru Berkah. Design/Methodology/Approach – This study employs a mixed-method approach by combining qualitative and quantitative methods. Data were collected through interviews, observations, and surveys. Using purposive sampling, six respondents were selected, consisting of one expert informant in supply chain management and five employees involved in relevant operational activities. The data were analyzed using the Analytical Hierarchy Process (AHP) with Expert Choice 11 to assess GSCM performance and its impact on competitive advantage. Findings – The results indicate that the implementation of Green Supply Chain Management (GSCM) significantly influences the company’s competitive advantage, particularly in terms of competitive pricing, product quality, delivery reliability, innovation, and speed to market. The findings suggest that GSCM practices can serve as a strategic approach for improving business performance and strengthening market positioning. Originality/Value This research provides value by analyzing GSCM implementation using a mixed-method approach and AHP, offering new insights into how sustainability practices can enhance competitive pricing, product quality, and market responsiveness in small and medium-sized enterprises.